2023
DOI: 10.1111/jhn.13132
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of environmental factors with the polygenic risk scores of thinness‐related genes in preventing obesity risk in middle‐aged adults: The KoGES

Abstract: Background Some persons are genetically resistant to obesity, but only a few studies have evaluated thinness genes for preventing obesity. We aimed to investigate the association of polygenic variants with being underweight and their interaction with the lifestyles of middle‐aged and elderly persons and identify potential new genetic approaches for managing body weight. Methods In total, 58,701 participants aged 40–77 years were recruited from urban hospitals in Korea. Underweight (case) was defined as body ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The significant modifying effect of diet was also demonstrated by Tan et al, who showed that individuals with higher PRS for obesity indeed presented higher levels of C-reactive protein but those levels appeared reduced in the presence of high dietary protein intake 18 . Similarly, middle-aged individuals with a higher genetic risk score for thinness presented lower body weight; an association aggravated with high protein and low carbohydrate intake, among others 19 . The multidisciplinary character of genetic risk-associated interactions is evident throughout the reciprocal interplay between the formation of anthropometric characteristics' levels and the formation of the lifestyle choices surrounding them.…”
Section: Prs Interactions With Lifestyle Determinantsmentioning
confidence: 95%
“…The significant modifying effect of diet was also demonstrated by Tan et al, who showed that individuals with higher PRS for obesity indeed presented higher levels of C-reactive protein but those levels appeared reduced in the presence of high dietary protein intake 18 . Similarly, middle-aged individuals with a higher genetic risk score for thinness presented lower body weight; an association aggravated with high protein and low carbohydrate intake, among others 19 . The multidisciplinary character of genetic risk-associated interactions is evident throughout the reciprocal interplay between the formation of anthropometric characteristics' levels and the formation of the lifestyle choices surrounding them.…”
Section: Prs Interactions With Lifestyle Determinantsmentioning
confidence: 95%